Making the Most of Cognitive Surplus: Descriptive Case Studies of Student-Generated Open Educational Resources - Mais Fatayer; Eseta Tualaulelei (MDPI AG, 2023)
Universities are hives of knowledge production and innovation, but the work students produce for assessment is often utilised in a limited way, neglecting a potentially rich intellectual resource. This article investigates an activity that can make use of this resource. It has known benefits for students but is rarely used in higher education-student-generated open educational resources (OER). In descriptive case studies of two projects where students created OER as an assessed part of university coursework, the article explores the impacts of this activity on students' learning experiences and the educational practice of teaching academics. Drawing upon social constructivist understandings of teaching and learning and a range of quantitative and qualitative data from projects with 156 students and 3 academics, the descriptive case studies illustrate how student-generated OER, guided by an OER development model, positively benefitted learners and educators. The discussion balances these benefits against some of the challenges experienced in the process. The article will argue that student-generated OER could be widely used, but specific supports are necessary for academics to facilitate this activity successfully.